FACTORS THAT CREATE CUSTOMER LOYALTY IN THE COLD BEVERAGE BUSINESS SECTOR: A STRATEGIC ANALYSIS - Muh. Husriadi; Rahman; La Ode Muhammad Sardin (CV. Adiba Aisha Amira, 2025)
Customer loyalty is a key factor in the success of a cold drink business, especially in Kendari City which experiences intense competition. This research aims to identify factors that influence customer loyalty in cold drink businesses in Kambu and Mandonga Districts, Kendari City. The research method used was a qualitative method, with in-depth interviews with cold drink business actors in the two sub-districts. The research results show that product quality, customer service, price, promotions and consumer experience are the main factors that influence customer loyalty. Measuring customer satisfaction through direct feedback and satisfaction surveys provides insights used for continuous improvement in products and services. The implications of this research show that a proactive and responsive approach to customer needs can increase loyalty and business sustainability. This research makes an important contribution to the customer loyalty literature and offers practical suggestions for cold drink businesses in increasing customer satisfaction and loyalty.